Kesan Pengupayaan Ke Atas Prestasi Pekerja Firma Milik Tempatan - Mohammad Rokhimi, Ahmad (2000)
This research tries to investigate whether wholly local firms practices empowerment in their organization and whether there are any relationships between empowerment and the workers performance, negative or positive relationship. The are a lot of indications towards identifiying the practice of empowerment in an organization. This research picks 3 aspects of empowerment, that is, communication, participation and teamwork. This research is a descriptive and a hipothetical test research on the independent variable, empowerment, and dependent variable, workers performance. 601 respondent have been taken as samples from 3 firms in the Kamunting Industrial Estate. Research results identifies a moderate environment of empowerment in all three firms with the min for all three aspects of empowerment listing between 3.1 to 3.3, referring to Likert’s scale 1 to 5. Furthermore, research results also indicates a moderate to high relationship between empowerment and workers performance in the three firms according to R2 statistic and Pearson correlation coefficient. Research results are in line with the research theory and this proves that workers performance is influence by empowerment. Nevertheless, the research only consider 3 of the many aspects of empowerment and is done in firms with production orientation. Research would be more interesting if all aspects of empowerment are considered and expended to firms of service background.